MEMAHAMI EMOTIONAL ROLES AND CONNECTIONS DALAM LIVE STREAMING SENIOR INFLUENCER: DAMPAKNYA TERHADAP PENINGKATAN PURCHASE INTENTION GENERASI Z - Putu Sri Suryani; Ni Kadek Winda Yanti (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2025)
The purpose of this study is to determine the influence of audience interaction, emotional appeal, and credibility of senior live streamers on Generation Z's purchasing interest in Denpasar, Bali, especially on the TikTok platform. The author used a survey method, where the study focused on Generation Z users in the Denpasar area who actively watch senior live streaming content on the TikTok platform. This population includes various groups, including students, young workers, and the general public who are digitally active, with a focus on Generation Z who are the dominant users of the platform. The technique used in this study's sampling is non-probability sampling. The results show that Gen Z audience engagement, active two-way interactions, such as comment responses and live question and answer sessions, can create a sense of belonging and increase audience engagement. Furthermore, emotional appeals built through inspirational narratives, humor, or content relevant to everyday life have been shown to strengthen parasocial bonds and drive purchase intention. Based on the coefficient of determination (R-square) analysis of 56.8%, it can be concluded that there are still 43.2% of factors outside the model that influence Generation Z's purchase intention. Therefore, future researchers are advised to add other variables such as social influence, brand trust, perceived value, or content quality to the research model, either as independent or intervening variables, to provide a more comprehensive explanation of the factors influencing Generation Z's purchase intention.